Comprehensive analysis of genes involved in the oxidative stress tolerance using yeast heterozygous deletion collection. Issue 3 (3rd February 2014) - Okada, Natsumi; Ogawa, Jun; Shima, Jun
Abstract In Saccharomyces cerevisiae, oxidative stress plays an inhibitory role during industrial fermentation. Although previous reports have identified genes required for oxidative stress tolerance, employing the yeast genome‐wide screening, these screenings used a homozygous mutant collection which did not include the essential genes whose deletions result in lethality. Here, we report a truly genome‐wide screening for the genes required for oxidative stress tolerance, using a heterozygous mutant collection which includes both essential and nonessential genes. Approximately 6300 heterozygous deletion mutants were grown in the presence or absence of H2O2. The screening identified a total of 331 genes whose heterozygotes conferred hypersensitivity to H2O2, indicating that these genes are required for oxidative stress tolerance. Notably, among these genes, 71 were essential genes. We classified these 71 essential genes based on localization, indicating that the localization of gene products from these essential genes was enriched in the nucleus and nucleolus. Classification of these essential genes based on functional categorizations showed that rRNA synthesis and tRNA synthesis were over‐represented, suggesting that nuclear function, such as RNA synthesis, is important in the response to oxidative stress. These results provide a helpful resource for the understanding of the molecular basis of oxidative stress‐tolerant mechanisms.